Peran Dan Fungsi Pengawasan Ketenagakerjaan Dalam Mencegah Pelanggaran Hak Tenaga Kerja Di Indonesia - Sutanti, Karisma Putri Tri (Jurnal JURISTIC, 2024)
Labor inspection plays a crucial role in ensuring that companies in Indonesia comply with applicable labor regulations, which aim to protect labor rights and ensure decent working conditions. This research aims to analyze the effectiveness of the role of labor inspection in ensuring compliance with labor regulations in Indonesia, especially those regulated in Law Number 13 of 2003 concerning Manpower and other related regulations. Using descriptive research methods, this research evaluates various indicators such as types of violations that frequently occur, frequency of inspections, responsiveness to violation reports, and duration of case handling. Data was collected through literature studies, interviews with labor inspection officers, and analysis of annual reports from relevant agencies. The impact of supervisory measures is measured through several indicators, including increased compliance with labor regulations, improved working conditions, reduced frequency of violations, and increased workforce satisfaction. The research results show that although labor inspection has had a positive impact in increasing compliance and improving working conditions, there are still various challenges that need to be overcome. These challenges include limited resources, lack of training for supervisors